2011
DOI: 10.1002/mana.200910270
|View full text |Cite
|
Sign up to set email alerts
|

Point mass insertion on the real line and non‐exponential perturbation of the recursion coefficients

Abstract: Abstract. We present the construction of a probability measure dγ with compact support on R such that adding a discrete pure point results in changes in the recursion coefficients without exponential decay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The reader may also refer to [33] in which Wong demonstrated that point perturbation of a certain class of measures on the real line would result in non-exponential perturbation of the recurrence coefficients.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The reader may also refer to [33] in which Wong demonstrated that point perturbation of a certain class of measures on the real line would result in non-exponential perturbation of the recurrence coefficients.…”
Section: Resultsmentioning
confidence: 98%
“…33) In other words, the Verblunsky coefficients of dµ y are 0, α 0 (dν y ), 0, α 1 (dν y ), 0, α 2 (dν y ) . .…”
Section: Proof Of Theorem 23mentioning
confidence: 99%